2021
DOI: 10.1088/1755-1315/800/1/012015
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of lead (Pb) and mercury (Hg) in green mussel Perna viridis (Linnaeus, 1758) in Cengkok Coastal Waters, Banten Bay, Indonesia

Abstract: Banten Bay potentially receives pollutants such as heavy metals from various anthropogenic activities operating around the bay. Cengkok Coastal Waters, as part of Banten Bay, has a variety of fishery commodities, including green mussels (Perna viridis). This paper identifies the risks of heavy metal contamination by quantifying the bioaccumulation of Pb and Hg in the green mussel tissue. The study was conducted from March to August 2019. Analytical results indicate concentrations of Pb and Hg in the range of 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…Cadmium metal (Cd) waste comes from agricultural waste (use of inorganic fertilizers and pesticides), battery industry, and plastic stabilizers [22]. According to [8], lead (Pb) metal waste comes from industrial activities, domestic waste, agricultural waste.Heavy metal copper (Cu) is an essential heavy metal needed by the body of living organism in small amounts. The source of heavy metal copper (Cu) in the waters of Banten Bay comes from ship transportation activities and steam power plant (PLTU) activities that use coal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cadmium metal (Cd) waste comes from agricultural waste (use of inorganic fertilizers and pesticides), battery industry, and plastic stabilizers [22]. According to [8], lead (Pb) metal waste comes from industrial activities, domestic waste, agricultural waste.Heavy metal copper (Cu) is an essential heavy metal needed by the body of living organism in small amounts. The source of heavy metal copper (Cu) in the waters of Banten Bay comes from ship transportation activities and steam power plant (PLTU) activities that use coal.…”
Section: Discussionmentioning
confidence: 99%
“…There have been many studies to the content of heavy metals in shellfish, including [6] studied heavy metals in mud clam (Geloina erosa) in East Segara Anakan and West of the Donan River (Cilacap), [7] studied heavy metals in green mussels (Perna viridis) in Trimulyo waters (Semarang), and [8] observed heavy metals in green mussels (Perna viridis) in Cengkok Coastal Waters, Banten Bay. In addition, research related to heavy metals in aquatic biota in Banten Bay were carried out, including [9] studied heavy metals in crab (Portunus pelagicus), [10] studied heavy metal in swimming crab (Scylla serrata), and [11] observed heavy metal in mud grouper (Epinephelus coioides).…”
Section: Introductionmentioning
confidence: 99%
“…Mullets Planiliza subviridis (Valenciennes, 1836) are one of the fish species living in the waters of the estuary with high tolerance to changes in water conditions, and the ability to adapt to a variety of food in their habitat (Nuringtyas et al, 2019). Research related to heavy metals in biota in the waters of Banten Bay has been carried out by several researchers, including the blue swimming crab (Febrianessa et al, 2020) and green mussels in Cengkok coastal waters (Melinda et al, 2021). These studies showed that the heavy metals that contained in the flesh of biota were still below the values of the quality standards.…”
Section: Introductionmentioning
confidence: 99%
“…Research on heavy metals in several other biota in Banten Bay were carried out by several researchers, including mud crab [7], blue swimming crab [8], green mussels [9], blood cockle [10] at Cengkok Beach, Banten Bay waters. Research related to the ecology of the Banten Bay waters was carried out by [11] and [12].…”
Section: Introductionmentioning
confidence: 99%